2002
DOI: 10.37855/jah.2002.v04i02.21
|View full text |Cite
|
Sign up to set email alerts
|

Yield and nitrogen recovery of lettuce under different irrigation regimes.

Abstract: Studies were conducted to determine the effect of irrigation regime on yield and nitrogen recovery of field grown lettuce in the Bekaa Valley of Lebanon, under non limiting soil N conditions. Within the experimental plots, irrigation differentiation was made upon crop evapotranspiration (ETc) measured on a non-weighing lysimeter of 16 m². The treatments included a control, I-100, irrigated at 100% of ETc, and two water deficit treatments, I-80 and I-60, irrigated at 80% and 60%, of ETc, respectively. Prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
20
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 14 publications
9
20
1
2
Order By: Relevance
“…Therefore, the decreasing of nutrients content in cabbage plant at 65% DASM may be due to redacting the solubility of mineral in the soil; hence movement of cations to root is reduced (Frank and Viets, 1967). The same trend was found by Karam et al (2002) who found that the highest nitrogen uptake was observed in lettuce plants of the well-irrigated treatment and it decreased with increasing water stress level. As regard to nitrate accumulation, the results show that there is a general significant negative effect on the nitrate content in inner leaves due to increasing each of available soil water in root zone (Table,5).…”
Section: N P K and No3 Accumulationsupporting
confidence: 86%
“…Therefore, the decreasing of nutrients content in cabbage plant at 65% DASM may be due to redacting the solubility of mineral in the soil; hence movement of cations to root is reduced (Frank and Viets, 1967). The same trend was found by Karam et al (2002) who found that the highest nitrogen uptake was observed in lettuce plants of the well-irrigated treatment and it decreased with increasing water stress level. As regard to nitrate accumulation, the results show that there is a general significant negative effect on the nitrate content in inner leaves due to increasing each of available soil water in root zone (Table,5).…”
Section: N P K and No3 Accumulationsupporting
confidence: 86%
“…The results of this study are, therefore, consistent with the literature (Karam et al, 2002; Coelho et al, 2005; Kuslu et al, 2008; Capra et al, 2008; Mansuroğlu et al, 2011; Bozkurt et al, 2009; Bozkurt and Mansuroğlu, 2011) concerning the importance of eliminating root water uptake deficit by managing irrigation to meet 100% of the ET demand. The results are also consistent with the general understanding that Ca‐related physiological disorders are associated with short periods of limited Ca 2+ supply to the plant, which is itself associated with limited water fluxes.…”
Section: Resultssupporting
confidence: 92%
“…The rates of Et were low at the early stages of vegetative growth (from 1 to 15 days after transplanting, DAT), then increased gradually (from 16 to 57 DAT) by the end of the growing season, when crops had reached the maximum number of mature leaves in the experiment. Likewise, Karam et al (2002) and Bozkurt et al (2009) demonstrated similar results in their study. There was a significant polynomial relationship (R 2 =0.96 in TDI, R 2 =0.82 in SDI 10 and R 2 =0.93 in SDI 20 treatments) between the lettuce yield and the crop Et as shown in Figure 2.…”
Section: Irrigation and Water Use Characteristicssupporting
confidence: 83%